UPAYA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN ANAK-ANAK MELALUI MAGRIB MENGAJI Di NAGARI KURANJI HILIR, KORONG LAMPANJANG, KECAMATAN SUNGAI LIMAU - Ningsih, Aulia Fitri (Education For All, 2022)
Abstract The Koran is the main worship since the beginning of the development of Islam in Indonesia, but in fact nowadays people are experiencing a shift in behavior so that the Koran is increasingly abandoned by Muslims in Indonesia. The Koran community movement program was appointed to overcome the problems that existed in the community. The Maghrib Koran program is a program to cultivate the habit of reading the Qur'an after the Maghrib prayer among the community. Reading the Qur'an or reciting the Koran which has long been a culture of Indonesian society. In writing this article, the study uses literature relating to the methods of collecting library data, reading and taking notes, and managing research materials (Zed, 2008: 3). The results of the research study explain that lately the Koran has begun to be abandoned. The mosques are empty, there are no more recitation activities. They are more engrossed in front of the television, gathering, playing big and doing other activities than reading the Koran. Thus, there is a need for a proper program to overcome these problems. The participation of parents and the community is needed to develop children's interest in reading the Qur'an, so that later children will have behavior and mutual respect among members of the community.